Exception Handling in a Strongly Typed Object Oriented Language - Rodriguez, Noemi; Ierusalimschy, Roberto; Rangel, José Lucas (Anais do Simpósio Brasileiro de Engenharia de Software (SBES); 1995: Anais do IX Simpósio Brasileiro de Engenharia de SoftwareDO - 10.5753/sbes.1995.24082, 1995)
This paper describes a proposal for combining exception handling and static type check ing in an object oriented language. Basic issues for exception handling mechanisms, such as termination versus resumption and the association between signaler and handler are discussed. The sub-typing rules of a statically checked OOL are extended in order to take exceptions into account. Finally, some examples are presented to illustrate the proposed mechanism.